Black boxes and open secrets: trilogues as 'politicised diplomacy'. Issue 3 (16th April 2021) - Roederer-Rynning, Christilla; Greenwood, Justin
Abstract: Why do EU actors promote secluded fora of decision making even as they have committed themselves to open and public lawmaking? How do they perceive and reconcile the ensuing tensions in practice? These questions, arising amidst growing public controversy, point to a blind spot in the scholarly agenda on EU lawmaking, which has overwhelmingly focused on the games institutions play. From an interpretivist perspective, we argue that rules are 'made' not by detached officials, but by practitioners puzzling out the meaning of their actions in their everyday experiences. Based on extensive interview material, the article captures trilogues as 'politicised diplomacy' and shows how they have become a 'permeable institution', shaped by dense flows of exchange between 'insiders' and 'outsiders'. The article helps pinpoint to what extent and how trilogues challenge democratic norms; and it punctures the myth of trilogues as quiet politics dominated by producer interests.